Association of CYP2D6 polymorphisms and extrapyramidal symptoms in schizophrenia patients receiving risperidone: a retrospective study - Takahiro Ito; Kazuhiro Yamamoto; Fuminori Ohsawa; Ikuo Otsuka; Akitoyo Hishimoto; Ichiro Sora; Midori Hirai; Ikuko Yano (BMC, 2018)
Abstract Background Risperidone is mainly metabolized by cytochrome P450 (CYP) 2D6 in the liver. The gene encoding CYP2D6 is highly polymorphic. The average steady-state plasma concentration of risperidone active moiety is higher in the CYP2D6 intermediate metabolizers (IMs) compared with that in the extensive metabolizers (EMs). An association between drug-induced extrapyramidal symptoms scale (DIEPSS) score and CYP2D6 polymorphisms has not been reported to date. This study investigates the association of CYP2D6 polymorphisms with the severity of extrapyramidal symptoms in schizophrenia patients receiving risperidone therapy. Methods Schizophrenia patients undergoing risperidone treatment were recruited for the study in the Kobe University Hospital. We evaluated extrapyramidal symptoms of schizophrenia using the DIEPSS. CYP2D6*10 and CYP2D6*14 were analyzed using TaqMan® assays, and CYP2D6*5 was analyzed using the long-PCR method. Patients with CYP2D6*1/*5, *1/*14, *5/*10, *10/*10, and *10/*14 were classified as IMs, and patients with CYP2D6*1/*1 and *1/*10 were classified as EMs. Patients with CYP2D6*5/*5, *5/*14, and *14/*14 were classified as poor metabolizers (PMs). Results A total of 22 patients were included in the study. No patients were classified as PMs. The dose of risperidone (mg/day) was not significantly different between EMs (n = 15) and IMs (n = 7) (median with the interquartile range: 4.0 (2.0-6.0) vs. 4.0 (2.0-7.0) mg, p = 0.31). The age and disease duration of schizophrenia were not significantly different between the EMs and IMs. The DIEPSS score in the IMs was significantly higher than that in the EMs (median with the interquartile range: 5.0 (3.5-6.5) vs. 0.0 (0.0-3.0), p < 0.001). The multiple regression analysis showed that CYP2D6 IMs is a significant risk factor for the DIEPSS (p < 0.05). Conclusion Special attentions should be paid to the onset of extrapyramidal symptoms in schizophrenia patients identified as CYP2D6 IM undergoing risperidone therapy.